Applying minimum income programs in Brazil two case studies: Belém and Belo Horizonte - Sônia Rocha (Institute for Applied Economic Research (ipea), 2015)
This paper examines the recent experiences of Belém and Belo Horizonte, two metropolitan nuclei where minimum income programs have been implemented. The idea is to verify to which extent the financial conditons in each of these municipalities seem to be compatible with the implementation of the program benefiting a significant share of the total number of the local poor. Alternatives will be considered for defining the target population in terms of income and family characteristics, as well as for establishing the value of the monthly transfer. The paper initially focuses on Brasilia's experience as the basis for adopting the same policy in Belém and Belo Horizonte. Next it describes the characteristics of program design and operation in Belém and Belo Horizonte. Despite the fact that the two municipalities present quite different characteristics, which, in their turn, are quite diverse from Brasilia's, both programs essentially adopted most operational parameters from the Federal District's program. Data from the National Household Survey are used to evidence the operational limits which the program faces in these two municipalities, given the size of the target population and the financial restrictions. Specific recommendations are presented to improve program's efficiency in each case.
Keywords: 330